Impact of Electronic Cigarette Smoking on the Saudi Population: A Systematic Review - Turki Fahad Alsabhan; Khaled F. Alrimali (International Journal of Medical Toxicology and Legal Medicine, 2024)
Objectives: This study is a comprehensive review and analysisof literature to investigate the patterns and attitudes surrounding e-cigarette use among the Saudi population over a period of six years. Review methods: A comprehensive search was conducted on Medline, PubMed, CINHIL, and ScienceDirect using the following alternate terms for e-cigarettes: electronic cigarettes, electronic nicotine delivery systems. The Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) diagram guided the inclusion of the studies published from 2018 to 2024. Results: Six studies were found fit to be included in this review, revealing the impacts and determinants of the usage and attitudes toward e-cigarette smoking among the Saudi population. The usage of e-cigarettes was high among the Saudi population and a wide variety of reasons were recorded for the use of e-cigarettes. Amongst these, lower costs, peer influence, curiosity, quitting traditional smoking, stress relief, flavor enjoyment were the significant factors identified. Conclusion: The findings underscore the significance of recognizing the harmful impacts of smoking and usage of other/ any type of tobacco, the roles of public health systems and health policy are critical to eliminate smoking and control the aggressive e-cigarettes marketing.